PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN DISPOSISI MATEMATIS SISWA SMP MELALUI MODEL PROBLEM BASED LEARNING - Rianti Rahmalia; Hajidin Hajidin; BI. Ansari (Jurnal Numeracy, 2020)
Mathematical communication skills of students are still relatively low. One learning model can improve students 'mathematical communication skills and at the same time students' mathematical disposition is the Problem Based Learning (PBL) model. The aim to be achieved is to find out the improvement of students 'mathematical communication skills and mathematical disposition using PBL models in terms of students' initial mathematical level. This research is an experimental research design with pretest posttest control group design. The research population was Grade VII students of SMP 9 Langsa. Students are grouped into two classes namely the experimental class and the control class randomly selected from eight parallel classes. The instrument used was a test of mathematical communication skills and a mathematical disposition questionnaire. Data analysis was performed using two-way ANOVA. The results showed that improving students 'mathematical communication ability and students' mathematical disposition by applying PBL learning models is better than students applying conventional learning models. There is no interaction between the PBL learning model with student level on mathematical communication skills and students' mathematical disposition. Abstrak Kemampuan komunikasi matematis siswa masih tergolong rendah. Salah satu model pembelajaran dapat meningkatkan kemampuan komunikasi matematis siswa dan sekaligus disposisi matematis siswa adalah model Problem Based Learning (PBL). Tujuan yang ingin dicapai ialah untuk mengetahui peningkatan kemampuan komunikasi matematis siswa dan disposisi matematis menggunakan model PBL ditinjau dari kemampuan awal matematis siswa. Penelitian ini merupakan penelitian eksperimen dengan desain pretest postest control group design. Populasi penelitian adalah siswa kelas VII SMP Negeri 9 Langsa. Siswa dikelompokkan menjadi dua kelas yaitu kelas eksperimen dan kelas kontrol yang dipilih secara acak dari delapan kelas paralel. Instrumen yang digunakan tes kemampuan komunikasi matematis dan angket disposisi matematis. Analisis data dilakukan dengan menggunakan anova dua arah. Hasil penelitian menunjukkan bahwa peningkatan kemampuan komunikasi matematis siswa dan disposisi matematis siswa dengan menerapkan model pembelajaran PBL lebih baik dari pada siswa yang menerapkan model pembelajaran konvensional. Tidak terdapat interaksi antara model pembelajaran PBL dengan level siswa terhadap kemampuan komunikasi matematis dan disposisi matematis siswa. Kata Kunci: Komunikasi Matematis, Disposisi Matematis, Problem Based Learning